INNOVATION OF ISLAMIC RELIGIOUS EDUCATION TEACHING MATERIALS BASED ON QUICK RESPONSE CODES FOR GRADE VII STUDENTS OF SMP NEGERI 6 LUBUKLINGGAU - Fitra Laila (Teaching and General Education Studies, 2026)
This study investigated the innovation of Quick Response (QR) code-based teaching materials in Islamic Religious Education for seventh-grade students at SMP Negeri 6 Lubuklinggau. The research was motivated by students’ low enthusiasm and limited understanding of learning materials, particularly the history of Prophet Muhammad SAW’s struggle during the Medina period. Teachers mainly relied on conventional textbooks, which reduced students’ motivation and engagement. Using a qualitative field research design, data were collected through observation, interviews, and documentation from May to July 2023. The findings revealed that learning innovations had already been implemented through conventional teaching and internet-assisted learning, such as practical videos on prayer and ablution. Furthermore, QR code-based teaching materials were found to increase students’ interest, motivation, and understanding because they were practical and easily accessible. The study also identified several supporting and inhibiting factors influencing implementation, including students, environment, facilities, and parental support in the learning process.